Determination of allele distribution of CYP1A2 gene rs762551 polymorphism on caffeine metabolism in healthy individuals - ULUCAN, KORKUT (My University, 2021)
Aims: The aim of the study was to determinate the CYP1A2 gene rs762551 polymorphism responsible for caffeine in healthy individuals. Study Design: DNA was isolated from saliva samples taken from healthy individuals. Analysis of A and C allele distribution of CYP1A2 gene rs762551 polymorphism was performed by amplifying DNA regions from individuals. Place and Duration of Study: It was carried out between February 2019 and April 2020 in Üsküdar University Medical Genetics and Molecular Diagnosis Laboratory. Methodology: Thirty healthy individuals without age, gender, height and weight restrictions were included in our study. DNA analysis was performed on the Real-Time PCR device by taking saliva samples from individuals. Results: The genotype distribution of this study was 13 people (43.33%) had AA, 9 people had AC (30%) and 8 people have a CC genotype (26.67%) respectively. According to the results of the study, individuals with the AA genotype are in the majority, but since there are more individuals with the C allele, those who metabolize caffeine slowly are in the majority. In our study, statistical analysis was not performed because it was aimed only to determine the allele gene distribution. Conclusion: Studies show an association between caffeine and disease. However, the genetic reasons for this relationship have not been fully understood yet. Therefore, more studies are needed on larger samples of genes that metabolize caffeine. Caffeine-related diseases can be prevented by detecting variations on caffeine genes of healthy individuals with more studies in the future.
Keywords: Caffeine intake; Genotyping; CYP1A2; Rs76255; Healthy individual